2019
DOI: 10.1186/s12951-019-0522-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phospho-peptide on the stability of gold nanoparticles and drug delivery

Abstract: Background Gold nanoparticles (AuNPs) have been proposed for many applications in medicine and bioanalysis. For use in all these applications, maintaining the stability of AuNPs in solution by suppressing aggregation is paramount. Herein, the effects of amino acids were investigated in stabilizing AuNPs by rationally designed peptide scaffolds. Results Compared to other tested amino acids, phosphotyrosine (pY) significantly stabilized AuNPs. Our results indicated that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Nanoparticles have also been conjugated with peptide/ amino acid in order to produce effective and targeted delivery systems. Synthesis of AuNPs conjugated with aspartic acid, 14 glutamic acid, phenylalanine and tryptophan, 202 L-cysteine, 203 lysine, 204 and peptides 15,205 has been reported. Amino acids and peptides bind with negatively charged AuNPs through amine groups, whereas the negatively charged carboxylic groups extend outwards to stabilize AuNPs.…”
Section: Peptides and Amino Acid Conjugationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles have also been conjugated with peptide/ amino acid in order to produce effective and targeted delivery systems. Synthesis of AuNPs conjugated with aspartic acid, 14 glutamic acid, phenylalanine and tryptophan, 202 L-cysteine, 203 lysine, 204 and peptides 15,205 has been reported. Amino acids and peptides bind with negatively charged AuNPs through amine groups, whereas the negatively charged carboxylic groups extend outwards to stabilize AuNPs.…”
Section: Peptides and Amino Acid Conjugationmentioning
confidence: 99%
“…The results have shown that phospho-tyrosine modified AuNPs when used as a delivery vehicle for doxorubicin were more effective at killing SGC-7901 cells. 205 Another study reports the conjugation of peptide CALNN and its derivative CALNNR8 with AuNPs for targeting components present inside the cell. AuNPs with the size of 30 nm could cross the cell membrane more easily through the processes of endocytosis and micropinocytosis.…”
mentioning
confidence: 99%
“…When pY peptide was used to stabilize Au NPs, the phosphate group could be removed with phosphatase, which then aggregated and released the Au NP charge. A significant increase in phosphatase has been observed in many types of cancer, indicating that aggregation of nanoparticles can be regulated by phosphatase [55]. It was also noted that by modifying the gold surface with polyethylene glycol modified with thiol groups, high efficiency was confirmed in the protection of Au NPs, in particular against the release of gold while allowing the binding of a large amount of drug and testing them as a carrier [56].…”
Section: Gold Nanoparticlesmentioning
confidence: 99%
“…Interestingly, AuNPs have attracted great attention during the past decade owing to their facile synthesis and surface functionalization [ 12 ], along with high photothermal conversion capacity in the near infrared region (NIR) without harmful side effects in biological systems [ 13 15 ]. AuNPs can be used in NIR imaging of tumors, as they possess good photostability [ 16 ].…”
Section: Introductionmentioning
confidence: 99%